Colonization and shift of mollusc assemblages as a restoration indicator in planted mangroves in the Philippines - Salmo, Severino G, III (Archīum Ateneo, 2016)
We compared the mollusc assemblages of planted mono-specific Rhizophora mangroves of known different ages. As forest age increased, there was a shift in species composition, abundance and biomass of mollusc assemblages for all faunal types (infauna, epifauna and arboreal fauna). This shift was correlated with the changes in vegetation (increasing forest cover and above-ground biomass) and sediment characteristics (increasing organic matter and decreasing sand content). Some species dominate in young plantations (<10 years old; Pirenella cingulata) and in intermediate plantations (10–15 years old; Nerita polita), while other species only occur in mature plantations and natural mangrove stands (>15 years; Terebralia sulcata, Nerita planospira). The two former groups of species are mostly species of infaunal and epifaunal habitats, while the latter group is mainly composed of arboreal species. The shift in mollusc species composition and dominance may serve as a useful indicator of restoration patterns in planted mangroves.